Numerical Analysis of an FRP-Strengthened Masonry Arch Bridge - Simoncello, Nicolò; Zampieri, Paolo; Gonzalez-Libreros, Jaime; Perboni, Simone; Pellegrino, Carlo (Frontiers in Built Environment, 2020)
Historical masonry arch bridges are a fundamental part of the road and railway networks in Europe. Very often, due to factors such as lack of maintenance, increase of traffic loads, etc., these structures need interventions in order to guarantee their adequate structural performance. For this reason, an important research effort has been devoted in previous decades to study the behavior of masonry arches and to identify innovative techniques able to increase their ultimate capacity, such as fiber reinforced polymer (FRP) composites. In this paper, the results of an experimental campaign carried out on masonry arches strengthened with one FRP layer applied at the structure intrados are used to calibrate a numerical analysis model. Then, the model is used to predict the contribution that this type of strengthening would have had on the well-known Prestwood Bridge. The numerical results show that the hypothetical intervention of the Prestwood Bridge would imply an increase in the ultimate load of the structure, although it would be significantly lower than that usually obtained for the case of arches tested in laboratory.